2019
DOI: 10.1002/jcp.28731
|View full text |Cite
|
Sign up to set email alerts
|

Identification of EPHX2 and RMI2 as two novel key genes in cervical squamous cell carcinoma by an integrated bioinformatic analysis

Abstract: Cervical cancer is the fourth most common malignancy in women worldwide and cervical squamous cell carcinoma (CESC) is the most common histological type of cervical cancer. The dysregulation of genes plays a significant role in cancer. In the present study, we screened out differentially expressed genes (DEGs) of CESC in the GSE63514 data set from the Gene Expression Omnibus database. An integrated bioinformatics analysis was used to select hub genes, as well as to investigate their related prognostic signatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…25 The bioinformatics studies showed that CDC45 was up-regulated in the cervical cancer tissues and a high expression of CDC45 was correlated with longer overall survival of patients with cervical cancer. 28,29 Our findings were consistent with the previous studies, suggesting the robust bioinformatics analysis in this study. However, the expression of CDC45 may be investigated in the cervical cancer tissues with different clinical stages, which can further reveal the prognostic role of CDC45 in the cervical cancer.…”
Section: Discussionsupporting
confidence: 93%
“…25 The bioinformatics studies showed that CDC45 was up-regulated in the cervical cancer tissues and a high expression of CDC45 was correlated with longer overall survival of patients with cervical cancer. 28,29 Our findings were consistent with the previous studies, suggesting the robust bioinformatics analysis in this study. However, the expression of CDC45 may be investigated in the cervical cancer tissues with different clinical stages, which can further reveal the prognostic role of CDC45 in the cervical cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Among these, GSE63514 and GSE9750 have been analyzed together (26,27). Other studies have also mined the GSE63514 (28) and GSE9750 (29) datasets; only the GSE7410 dataset had not yet been thoroughly examined previously, to the best of our knowledge. Therefore, the GEO2R online tool was used to perform the analyses of the three datasets to determine any potentially relevant factors.…”
Section: Discussionmentioning
confidence: 99%
“…The ID corresponding to the probe name was converted into an international standard name for genes (gene symbol) and saved in a TXT file. If several probes were mapped to one gene symbol, the mean value was set as the final expression value of this gene (Irizarry et al, 2003;Liu et al, 2019) (Supplementary Table S1). Meanwhile, the expression profiles of messenger RNAs in 309 tissues (306 CESC tissues and 3 normal tissues) and the corresponding clinical information were downloaded from TCGA database.…”
Section: Figmentioning
confidence: 99%